2014
DOI: 10.7863/ultra.33.8.1373
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Intracranial Translucency and the Posterior Brain in Normal Fetuses at the 11‐ to 13‐Week Scan

Abstract: Intracranial translucency can be prospectively identified by trained sonographers in 96% of normal fetuses at 11 to 13 weeks. Measurements of brain stem and brain stem-occipital bone diameters are reproducible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
2
11
2
Order By: Relevance
“…Supine fetal position is consistently reported as significantly associated with IT visualization, as we also found in our study. However, authors have differed when assessing the affect of maternal BMI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Supine fetal position is consistently reported as significantly associated with IT visualization, as we also found in our study. However, authors have differed when assessing the affect of maternal BMI.…”
Section: Discussionsupporting
confidence: 90%
“…Mean maternal age was 29.2 years (16-42), mean maternal BMI was 24.5 kg/m 2 (14.7-58.4), mean CRL was 65.6 mm (47-84) and mean nuchal translucency thickness was 1.8 mm (0.9-7.7). Placental location was as follows: anterior (366), posterior (337), bilobed (1), lateral (10) and fundal (28). Fetal lie was as follows: supine (679), prone (8) and variable (55).…”
Section: Methodsmentioning
confidence: 99%
“…This rate was between 0% and 5% in other series. [4,[19][20][21] When we reviewed the literature, we found out that many studies on IT issue were rather archive studies which investigated recorded images retrospectively. [13,22,23] When these examinations were reevaluated, it was found that any fluid image seen in posterior fossa of some fetuses could be measured as IT by accident.…”
Section: Discussionmentioning
confidence: 99%
“…By performing sonographic examinations in this period (apart from other advantages), it is possible to identify signs of fetal malformations and various markers of aneuploidy. 2,[9][10][11][12][13] It has been shown that an alteration in the intracranial translucency values between 11 weeks and 13 weeks 6 days suggests a central nervous system defect. [14][15][16][17][18][19][20][21] Reduced intracranial translucency values have been associated with open spina bifida, 3,7,22,23 which is considered a congenital defect associated with high perinatal mortality and high long-term morbidity.…”
Section: Discussionmentioning
confidence: 99%